Economic Policy Uncertainty and Energy Prices: Empirical Evidence from Multivariate DCC-GARCH Models - Ringim, Salim Hamza; Alhassan, Abdulkareem; Gungor, Hasan; Bekun, Festus Victor (Mdpi, 2022)
Crude oil and natural gas are crucial to the Russian economy. Therefore, this study examined the interconnections between crude oil price, natural gas price, and Russian economic policy uncertainty (EPU) over the period 1994-2019 using multivariate DCC-MGARCH models. The findings show that there are strong interconnections (co-movement) between the energy prices and EPU in Russia, and that it might be misleading to assume independence or neutrality between the variables. Although Russia is also a crucial player in both the natural gas and the crude oil markets, this study reveals that there is a stronger co-movement of the EPU with gas price than with the oil price. Russia is the largest exporter of natural gas and the second-largest producer; it is plausible that the natural gas price correlates with EPU more than the crude oil price. Further, the correlation between gas price and EPU and the correlation between crude oil price and EPU have similar patterns. Each declines almost in the same period and, equally, increases concurrently. In addition, the results revealed that significant global shocks and crises, such as the 2008 global financial crisis, the 2014-2017 Russian financial crisis, the 9/11 terrorist attack, and the Russo-Ukrainian conflicts, influence the interconnections between the energy prices and Russian EPU.
Keywords: economic policy uncertainty; crude oil price; natural gas price; multivariate DCC-GARCH models